MATERNAL AND NEONATAL COMPLICATIONS IN GESTATIONAL DIABETES MELLITUS COMBINE MILITARY HOSPITAL PESHAWAR (The Research of Medical Science Review, 2025)
Gestational diabetes mellitus (GDM) is a pregnancy complication in which the placenta releases hormones that interfere with the body’s ability to use insulin effectively, leading to elevated blood glucose levels. This condition can have significant impacts on both maternal and neonatal health. GDM is characterized by spontaneous high blood sugar during pregnancy and can increase the risk of complications for both the mother and the baby. The objective of this study was to examine the maternal and neonatal complications in women diagnosed with GDM. This cross-sectional descriptive study was carried out at obstetrics and gynecology department in Combined Military Hospital Peshawar, from June 13, 2022 to December 13, 2022. One hundred and fourteen women participated in this study using a non-probability consecutive sampling technique. The study was to identify the maternal and neonatal consequences of gestational diabetes. The age breakdown of the participants exploded the following working ages 31-35 years (28.1%) and the 36-40 years (21.1%). The age of participants was also calculated from their provided birth dates, and the mean age was 36 years with standard deviation ± 2.87 years. As observed from the gestational age distribution most of the women delivered at full term in the range of 39-40 weeks (42.1%) followed by late term of 41-42 weeks (34.2%). The mean gestational age was taken as 35 weeks with a SD of plus/minus 6.818. For the type of diabetes, 81 women suffered from gestational diabetes 71.1%, and 33 (28.9%) had pre-existing diabetes mellitus. Some of the maternal complications were; PIH (15.8%), hypoglycemia (23.7%), PPH (33.3%) and Cesarean section delivery (27.2%). Poor perinatal outcomes were; congenital abnormalities, 33.3%, preterm births 21.9%, macrosomia 25.4% and neonatal hypoglycemia 19.3%. Increase awareness of the maternal and fetal complications of gestational diabetes are presented in these findings.Thus, adequate glycemic control in women with pregestational diabetes is crucial to lowering maternal and fetal morbidity. Luckily, these risks are manageable if high risk patients are first diagnosed then prevented after identification. Moreover, modification of the behaviors/states that are deemed to predispose women to GDM including; obesity, nutrition, etc are very important especially in women without diabetes before the conception. Education on these aspects can help to decrease the negative consequences that gestational diabetes mellitus has for a woman and her baby.